Alternatives for selecting the database design and management of operational data into libraries - Fernández, Mynor (2014)
One of the major tasks of any automation project is the units of information concerning the selection of the design of databases; however, it is important to note that often when you are selecting an application for automation generally a superficial analysis of the associated databases is paying little attention to the completeness of the databases and processing capabilities to meet the needs of information required, with the result that this way of proceeding is likely to lead to a failure of the automation project. This article discusses the different alternatives that are presented to the project team automation to select the design of databases that will support the automation project, in order to single out the most important aspects to consider are for each of the available options. You should always insist on any of the available alternatives requires careful and critical databases associated analysis and its ability to meet the information needs identified, operational and managerial Unit.